Undergraduate Students’ Readiness for Blended Learning during COVID – 19 Pandemic in Sri Lanka Investigating the availability of resources, characteristics of learners, technological skills and their belief on this method with compared to other learning m - Kumari, K.W.S.N.; Jayasinghe, G.J.M.S.R. (The journal of contemporary issues in business and government, 2021)
Recently, a major education crisis occurred around the world due to the COVID-19 pandemic. Consequently, Sri Lanka too, resorted to shutting down its universities. This created a need to find alternative learning methods to carry out educational activities during a challenging period. Therefore, this study was conducted to investigate the readiness of undergraduates for blended learning. The structured questionnaire was shared online to collect the necessary data. The sample of 549 undergraduates representing all universities was selected for the study by applying the convenient sampling method. The student's readiness was assessed using 28 questions. All of them had at least a smartphone to connect to the internet, but 48% of them had moderate speed internet connections. Exploratory factor analysis indicated that four factors are significant for readiness in learners' characteristics such as communication, interaction and study habits, technological skills, availability of resources, and their belief, in the blended learning method. Undergraduates' overall readiness percentage scores in four indicators were above 50% indicating a moderate amount of readiness in each area. According to the two-sample proportions test, among four areas, only readiness in resources and infrastructure was significantly different across gender. The majority of undergraduates preferred blended learning during the COVID-19. Although the government offers free internet service for educational websites, they should facilitate internet services to all areas in the country. Further, authorities in higher education would enhance students' awareness and skills on web-based learning.Additionally, undergraduates should be encouragedto adapt to blended learning during this type of challenging periods.